2018
DOI: 10.1016/j.bcmd.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Twelve years of experience with miglustat in the treatment of type 1 Gaucher disease: The Spanish ZAGAL project

Abstract: We report data from a prospective, observational study (ZAGAL) evaluating miglustat 100mg three times daily orally. in treatment-naïve patients and patients with type 1 Gaucher Disease (GD1) switched from previous enzyme replacement therapy (ERT). Clinical evolution, changes in organ size, blood counts, disease biomarkers, bone marrow infiltration (S-MRI), bone mineral density by broadband ultrasound densitometry (BMD), safety and tolerability annual reports were analysed. Between May 2004 and April 2016, 63 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…These included diarrhea, weight loss, tremor, and peripheral neuropathy. As a result, 49 of 115 patients discontinued use of miglustat after experiencing such side effects [120122].…”
Section: Therapeutic Treatment Goals For Gdmentioning
confidence: 99%
“…These included diarrhea, weight loss, tremor, and peripheral neuropathy. As a result, 49 of 115 patients discontinued use of miglustat after experiencing such side effects [120122].…”
Section: Therapeutic Treatment Goals For Gdmentioning
confidence: 99%
“…The iminosugar Miglustat (N-butyl-deoxynojirimycin), a registered oral agent to treat mild type 1 GD, markedly inhibits GBA2 activity at the administered dose (3 times 100 mg daily) (47). A very large number of type 1 GD patients have been treated with Miglustat for more than a decade without major side effects except for intestinal complaints due to inhibition of intestinal glycosidases (63). Apparently, in these individuals GBA2 inhibition has no overt detrimental consequences.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Miglustat has previously been shown to be an effective long-term maintenance treatment for core hematologic and visceral symptoms in GD [ 13 , 16 ], and studies suggest that it can produce significant improvements in bone status, reducing bone pain as early as 6 months after treatment start [ 15 ]. In both cases presented here, miglustat administered as monotherapy demonstrated satisfactory maintenance of core GD disease parameters in patients stabilized on ERT, as has been reported previously [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short-term clinical trials and long-term, open-label extension studies demonstrated the efficacy and safety of the first approved oral SRT, miglustat (Zavesca®, N-butyldeoxynojirimycin [NB-DNJ], Actelion Pharmaceuticals, Basel, Switzerland), in treating core hematologic and visceral symptoms of GD [ 11 13 ]. A long-term study has further shown that miglustat can be used as a maintenance therapy in patients with stable GD1 switched from previous ERT [ 14 ], and the effects of miglustat in improving bone pain and bone mineral density (BMD) over 2–12 years have been reported in other studies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%